A comparative evaluation of four DNA extraction protocols from whole blood sample - Ghaheri, M; Kahrizi, D; Yari, K; Babaie, A; Suthar, R S; Kazemi, E (Cellular and Molecular Biology, 2016)
All organisms have Deoxyribonucleic acid (DNA) within their cells. DNA is a complex molecule that contains all of the information necessary to build and maintain an organism. DNA extraction is one of the most basic and essential techniques in the study of DNA that allow huge advances in molecular biology, biotechnology and bioinformatics laboratories. Whole blood samples are one of the main sources used to obtain DNA and there are many different protocols available in this issue. In current research, compared four DNA extraction protocols from blood samples; include modified phenol-chloroform protocol, two salting-out and enzyme free method and from commercial kit. The extracted DNAs by these protocols were analyzed according to their time demands, quality and quantity, toxicity and functionality in PCR method. Also the quality and quantity of the extracted DNA were surveyed by gel electrophoresis and Nanodrop spectrophotometry methods. It was observed that there are not significantly differences between these methods about DNA Purity (A260/A280), but the DNA yield (ng DNA/Î¼l) of phenol/chloroform method was higher than other methods. In addition, phenol/chloroform was the most toxic method and it takes more time than other methods. Roche diagnostics GmbH kit was the most expensive among the four methods but the least extraction time was required and it was the safest method.